Efficacy of calcium carbonate in reducing the incidence of pre-eclampsia vis-a-vis calcium lactate - Ramani S; Vijaya B; Nithya B (Barpeta Obstetrics and Gynaecological Society, 2022)
Background: Pre-eclampsia remains an important maternal health problem in India. WHO makes a strong recommendation for supplementation of pregnant women with 1.5 grams to 2.0 grams of elemental calcium per day in areas with low dietary calcium intake and for women at high risk of developing hypertensive disorders during pregnancy. Objectives: 1) To evaluate the efficacy of calcium carbonate in reducing the incidence of pre-eclampsia and 2) to study the maternal and fetal outcomes, in antenatal women with hypertensive disorders of pregnancy. Methods: This was a prospective, observational study done in the department of obstetrics and gynaecology, Government Head Quarters Hospital, Dindigul, Tamil Nadu. 600 pregnant women in early second trimester, from 14 weeks to 20 weeks, attending during October 2018 to February 2020, were recruited. The subjects were divided into two groups of 300 each (calcium lactate and calcium carbonate). All the descriptive and inferential statistics were analysed using SPSS software 22 version. P value of <0.05 was considered statistically significant. Results: Of 600 antenatal mothers, 86 (14.3%) of them developed preeclampsia in both groups. 8(57%) mothers of both group, delivered low birth weight babies and 5(36%) of the babies in calcium lactate group and 3(17%) calcium carbonate group were admitted in NICU. 45 (100%) mothers of calcium lactate group had proteinuria and 15 (33.3%) of them had caesarean section. 40 (97.6%) of calcium carbonate group had proteinuria and 26 (63.4%) of them had caesarean section. Calcium carbonate group showed improved adverse maternal and fetal outcomes. Conclusion: It can be concluded that, calcium supplementation during pregnancy is effective in reducing the risk of pre-eclampsia and adverse maternal and neonatal outcomes associated with the condition.